A Facile Synthesis of Water‐Resistant CsPbBr3 Perovskite Quantum Dots Loaded Poly(methyl methacrylate) Composite Microspheres Based on In Situ Polymerization. Issue 22 (23rd August 2019) - Cai, Yuting; Li, Ye; Wang, Le; Xie, Rong‐Jun
Abstract: In this paper, a facile synthesis of water‐resistant CsPbBr3 perovskite quantum dots (PQDs) loaded poly(methyl methacrylate) (PMMA) composite microspheres (CsPbBr3 @PMMA) is reported. The method is based on the precipitation polymerization of methyl methacrylate in hexane in the presence of CsPbBr3 PQDs and stabilizer. The CsPbBr3 @PMMA microspheres show a tunable size and a narrow size distribution, with the CsPbBr3 PQDs being uniformly dispersed in the PMMA microspheres. The effective incorporation of PQDs is attributed to the strong coordination interactions between Pb ions on the surface of PQDs and carbonyl groups (CO) from PMMA. Based on this mechanism, multicolor composite microspheres can be easily prepared through absorbing CsPbX3 (X = Cl, Br, I) PQDs into blank PMMA microspheres. Protected by the PMMA microspheres, the imbedded CsPbBr3 PQDs show improved water resistance and storage stability. Further, a wide‐color‐gamut (129%) white light‐emitting diode (LED) is demonstrated by combining the green‐emitting CsPbBr3 @PMMA composite microspheres and red‐emitting K2 SiF6 : Mn 4+ with a blue LED, which enables to be used as backlights for liquid crystal displays. Abstract : CsPbBr3 perovskite quantum dots (QDs)‐loaded poly(methyl methacrylate) composite microspheres are easily prepared through in situ polymerization of methyl methacrylate in the presence of quantum dots in hexane. This method is very facile and the CsPbBr3 perovskite QDs are evenly incorporated into the microspheres. Protected by the microsphere, the water and storage stability of CsPbBr3 quantum dots are greatly improved.